ANALYSIS OF THE EFFECT OF EMPLOYEE TRAINING AND DEVELOPMENT ON EMPLOYEE ACHIEVEMENT PT PACIFIC MEDAN INDUSTRY MEDAN - Rosita, Rosita; Stefvy, Stefvy (Jurnal Manajemen dan Bisnis, 2021)
This study aims to describe the effect of employee training and development on employee performance at PT Pacific Medan Industry. This research uses simple random sampling method. Research respondents are part of the Marketing Department of PT. Pacific Medan Industry, totaling 85 (eighty five) people. The instrument used is a questionnaire to collect data from training variables, employee development variables, and employee performance variables, multiple linear regression analysis, multiple linear correlation coefficient tests, partial hypothesis testing or t test, simultaneous hypothesis testing or F test, and calculations. coefficient of determination. The results of the descriptive analysis for the training variable are in the fairly good category, the employee development variable and work performance are in the good category at PT Pacific Medan Industry. Industry. Simultaneously, employee training and development has a positive and significant effect on employee performance at PT Pacific Medan Industry. The contribution of training variables and employee development variables to the increase in employee performance variables at PT Pacific Medan Industry is 0.753 or 75.3%, while the remaining 0.247 or 24.7% is influenced by other variables not examined by the authors in this study. such as work motivation, work culture, work discipline, and so on.